The nexus of capital structure, profitability, and the covid-19 financial crisis: an empirical analysis of South African JSE listed firms. - Hove, Michael (Department of Finance and Tax, 2025)
This study explored the interplay between capital structure choices and financial performance across 72 JSE-listed firms, spanning 2008 - 2022. By employing panel data regression, the data sourced from financial reports underwent an analysis using descriptive statistics, correlation matrices, and fixed effects regression models. Findings revealed negative associations between debt ratios and profitability metrics over the full sample period. The study addressed the COVID-19 pandemic's influence, and the results were consistent even during the crisis. In conclusion, this research potentially presents invaluable insights for stakeholders navigating the dynamic landscape of capital structure decisions and their profound implications on financial performance within the South African market, even amidst the disruptive forces of a global pandemic. As more debt usage was found to have a negative effect on profitability, firms would have to make courteous decisions in adding more debt to their capital structure(s) to avoid its dire effects on the bottom line.